Etika Pengobatan/Rekayasa Genetik dalam Islam sebagai Implikasi untuk Terapi Gen dan Teknologi DNA serta Tantangan Kontemporer - Aiswah Zahra Amalia; Nur Hilmi (Jurnal Medika Nusantara, 2024)
Gene therapy offers the potential for treating genetic diseases and improving quality of life, but it also raises significant ethical challenges, including issues of genetic manipulation and eugenics. By identifying fundamental principles of Islamic ethics, this study explores how genetic technology can be integrated within an appropriate moral context. Through literature analysis and scholarly perspectives, this article highlights the need for dialogue among scientists, medical practitioners, and religious communities to establish guidelines for the use of this technology. The findings indicate that a balance between technological innovation and the preservation of Islamic ethical values is essential to ensure that scientific advancements provide benefits without violating moral principles. The article also recommends further research to explore the practical applications of gene therapy within the framework of Islamic ethics.